Unlocking the secrets of the hair microbiome: From scalp health to therapeutic advances - Jibon Kumar Paul; Mahir Azmal; Omar Faruk Talukder; ANM Shah Newaz Been Haque; Meghla Meem; Ajit Ghosh (The Microbe)
The human microbiome, a complex and dynamic community of microorganisms abiding in and on the human body, plays a critical part in maintaining health and impacting complaints. This microbiome includes bacteria, fungi, viruses, and other microbes that are essential for various physiological processes such as digestion, immune function, and pathogen protection. Among the different microbiomes in the body, the hair follicle microbiome is a distinct and vital niche. It influences hair and scalp health, including hair growth, immune responses, and forestallment of pathogenic colonization, and is involved in conditions like dandruff, seborrheic dermatitis, and acne. Recent exploration has begun to uncover the composition and functional places of the hair follicle microbiome, revealing its active participation in maintaining hair and scalp health. This review provides a comprehensive overview of the hair follicle microbiome, discussing its composition, functional roles, and relations with the host, and exploring methods to study these microbial communities. It highlights the remedial potential of targeting the hair follicle microbiome in treating hair and scalp conditions and suggests unborn exploration directions in this field.